Social psychology goes local: Foster, D and Louw-Potgieter, J (eds) (1991) Social psychology in South Africa. Johannesburg: Lexicon. - Campbell, Catherine (PINS-Psychology in Society, 2026)
Foster and Louw-Potgieter have produced an important book, long overdue in South Africa, namely one which provide a coherent and unified account of existing research into what is loosely referred to as the field of "inter-group relations" in South Africa. In the past, teachers and student of social psychology in this country have tended to rely on inappropriate European and American texts. Researchers have been faced with the wearisome task of tracking down local social psychological scholarship, scattered about in an unwieldy mass of books, chapters and journal articles, many of which were difficult to find. Against this rather inconvenient background Social psychology in South Africa provides timely and welcome relief.